High failure rate in mathematics subject: influencing factors and study styles / Zuraida Alwadood ... [et al.] - Alwadood, Zuraida; Abd Halim, Suhaila; Sulaiman, Hanifah; Mohd. Noor, Norlenda (Penerbit UiTM (UiTM Press), 2018)
The objectives of this study are to determine factors that contribute to the Engineering Calculus subject failures and to analyse the study styles of students taking this course. Based on the literature search, these factors are categorised into three domains which are students' attitude, students' background and teacher-related factors. A survey research was done to a sample of engineering degree students who are taking Engineering Calculus subject at their third semester. It was found that non-systematic study style is the greatest factor which has been claimed by the respondents as the main reason for their failures. Besides this, a majority of the students are comfortable with studying alone, as compared to taking part in study group or seeking help from lecturers. These findings suggest that corrective actions should be taken by the students, lecturers, as well as the faculty in order to cope with the alarming failure rate of mathema tics subject.